High temperature drying properties and basic drying schedule of 5 lesser-known species from Riau - Karnita Yuniarti; Efrida Basri (Jurnal Penelitian Kehutanan Wallacea, 2017)
Drying process is a crucial stage in the utilization of any wood for construction and furniture purposes. The study aimed to: (i) investigate the sensitivity of several lesser-known wood species from natural forest in Riau to drying process at high temperature; and (ii) develop basic drying schedule for each wood. Five lesser-known species from Riau were investigated, namely punak (Tetramerista glabra), mempisang (Diospyros korthalsiana), pasak linggo (Aglaia argentea), meranti bunga (Shorea teysmanniana) and suntai (Palaquiumburckii). Modified Terazawa’s (1965) method was used for the experiment. The result shows that deformation was found for all species. The most severe deformation level was observed for both punak (score value of 4-6) and mempisang (score value of 4-5). On the other hand, pasaklinggo experienced the most severe initial end/surface check/split (score value of 6) and honeycombing (score value of 5). The result also showed that punak and pasaklinggo can be dried with the same drying schedule at the temperature range of 40-65° C and the humidity range of 38-88%. The proposed temperature and humidity ranges (or drying schedules) are 50-80° C and 28-80% for suntai, 50-70° C and 25-80% for mempisang, and 50-70° C and 40-84% for meranti bunga. Mempisang and suntai can use the same drying condition until fiber saturation point, then different drying condition applies.